CYCLOSPORINE IN TREATMENT OF SEVERE ATOPIC DERMATITIS IN CHILDREN - A.A. Alekseeva ("Paediatrician" Publishers LLC, 2010)
Atopic dermatitis (AtD) is one of the most widespread types of allergic lesions of skin in children. Increase of severe types of AtD with lesion of big parts of skin, high frequency of exacerbations, presence of concomitant atopic diseases, and inefficiency of standard therapeutic approaches, torpid clinical course and early development of disability, causes an anxiety. Present standard approaches can be ineffective in children with severe clinical course of AtD and they are not able to prevent progression of disease, development of severe exacerbations and child's disability. One of therapeutic alternatives for these patients is treatment with immunosuppressive agents. The article describes questions of treatment with cyclosporine in systemic therapy of severe resistant forms of AtD in children. Author discusses effectiveness and safety of a drug, formulated rules of treatment of severe AtD with cyclosporine. Key words: children, atopic dermatitis, cyclosporine, treatment. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(5):117-120)